Sanitetna služba Maistrove vojske - Pivec, Gregor (Studia Historica Slovenica, 2015)
Based on accessible resources, the author discusses the formation of the Austrian army within the 3rd Army corps (Graz), i.e. units with soldiers of Slovene nationality. He also describes the broader political and military situation at the end of the First World War. The so-called Maister's Army, which initially included volunteers from the former units of the Austrian army, established its own structure-specific sanitary services. The services functioned on similar principles as all sanitary services of the then armies, partially relying on military and partially on civil healthcare institutions. Special emphasis was placed on the problem of military transport at the end of the war. Due to non-discipline of soldiers leading to numerous injuries, including the severe railway accident near Hajdina, the military transports were particularly challenging. In the end the author describes in brief the sanitary supply of Maister's fighters in battles across Carinthia.
Keywords: Maister, Rudolf; Maribor; saniteta; severovzhodna Slovenija; slovenska vojska; zgodovina